Eksistensi Komunitas Gubuk Harapan Di Desa Seberang Kecamatan Lamuru Kabupaten Bone Sulawesi Selatan - Hasrianto, Hasrianto; Sutrisno, Tri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
A community is an association of young people who form social groups which then interact with each other continuously. Communities are formed because of similarities, interests, attitudes, hobbies between individuals and then a forum is formed. The existence of a community is now increasingly widespread throughout Indonesia.  The development of this community also exists in Bone district, South Sulawesi. This community is in Seberang Village, Lamuru District, Bone Regency. The hope hut community has existed for quite a long time in Seberang Village, this community was formed on November 23 2020, located in Lawara Hamlet, Opposite Village, Lamuru District, Bone Regency, South Sulawesi Province until now. The Gubuk Harapan community tends to be different from other communities, the difference lies in the work program and objectives. This research uses a qualitative approach. Researchers must look at people's views. Research subjects or responders are people who are asked to provide information about facts and opinions. The results of this research is that the existence of a hope hut provides a very positive value so that everyone who joins in it shares the desire to develop knowledge through processes that may not be easy but are able to provide the best for children and the local community. So it can be concluded that communities or groups have similarities, interests, attitudes, hobbies between individuals, especially in the Hope hut community of Lawara Hamlet, Opposite Village, Lamuru District, Bone Regency, South Sulawesi Province.